User Experience Analysis of Learning Management System (LMS) SINAU to Support Learning with MERDEKA Flow Using UX Curve Method - Yarsasi, Sri; Tahyudin, Imam; Hariguna, Taqwa (Informatika, Universitas Jenderal Soedirman, 2026)
The rapid development of information technology has driven transformation in education, including the use of Learning Management Systems (LMS) to facilitate independent and flexible learning aligned with the Merdeka Curriculum. This study aims to evaluate the user experience (UX) of the Sinau LMS at SMA Negeri 1 Sidareja using the UX Curve method, which tracks changes in user perceptions over time. The research involved 20 grade XII students who had used the LMS for at least three months. Data were collected through initial questionnaires, interviews, UX curve drawings, and final questionnaires, focusing on five main UX aspects: General UX, Attractiveness, Ease of Use, Utility, and Degree of Usage. The analysis of 100 curves revealed that more than half of the respondents experienced a decline in user experience quality, particularly in Ease of Use, General UX, and Degree of Usage, due to issues such as an unattractive interface, navigation challenges, and limited feature relevance. Conversely, a minority showed improved perceptions as they adapted and became more familiar with the system. These findings highlight the need for continuous improvement of the LMS's interface design and features to enhance user satisfaction and learning effectiveness. The study contributes theoretically by demonstrating the application of the UX Curve in educational systems and practically by providing recommendations for refining LMS development to better support the Merdeka Curriculum.